Adaptive paediatric investigation plans, a small step to improve regulatory decision making in drug development for children?. (12th July 2016) - Bauer, Peter; König, Franz
Abstract : Different arguments have been put forward why drug developers should commit themselves early for what they are planning to do for children. By EU regulation, paediatric investigation plans should be agreed on in early phases of drug development in adults. Here, extrapolation from adults to children is widely applied to reduce the burden and avoids unnecessary clinical trials in children, but early regulatory decisions on how far extrapolation can be used may be highly uncertain. Under special circumstances, the regulatory process should allow for adaptive paediatric investigation plans explicitly foreseeing a re‐evaluation of the early decision based on the information accumulated later from adults or elsewhere. A small step towards adaptivity and learning from experience may improve the quality of regulatory decisions in particular with regard to how much information can be borrowed from adults. © 2016 The Authors. Pharmaceutical Statistics Published by John Wiley & Sons Ltd.